MTORC2 sustains thermogenesis via Akt‐induced glucose uptake and glycolysis in brown adipose tissue. Issue 3 (15th January 2016) - Albert, Verena; Svensson, Kristoffer; Shimobayashi, Mitsugu; Colombi, Marco; Muñoz, Sergio; Jimenez, Veronica; Handschin, Christoph; Bosch, Fatima; Hall, Michael N
Abstract: Activation of non‐shivering thermogenesis (NST) in brown adipose tissue (BAT) has been proposed as an anti‐obesity treatment. Moreover, cold‐induced glucose uptake could normalize blood glucose levels in insulin‐resistant patients. It is therefore important to identify novel regulators of NST and cold‐induced glucose uptake. Mammalian target of rapamycin complex 2 (mTORC2) mediates insulin‐stimulated glucose uptake in metabolic tissues, but its role in NST is unknown. We show that mTORC2 is activated in brown adipocytes upon β‐adrenergic stimulation. Furthermore, mice lacking mTORC2 specifically in adipose tissue (AdRiKO mice) are hypothermic, display increased sensitivity to cold, and show impaired cold‐induced glucose uptake and glycolysis. Restoration of glucose uptake in BAT by overexpression of hexokinase II or activated Akt2 was sufficient to increase body temperature and improve cold tolerance in AdRiKO mice. Thus, mTORC2 in BAT mediates temperature homeostasis via regulation of cold‐induced glucose uptake. Our findings demonstrate the importance of glucose metabolism in temperature regulation. Synopsis: Albert et al show that β‐adrenergic stimulation activates mTORC2 in brown adipocytes. Active mTORC2 signaling in BAT is required for cold‐induced stimulation of glucose uptake and glycolysis to maintain temperature homeostasis upon cold stress. β‐adrenergic stimulation activates mTORC2 in brown adipocytes. Mice deficient for mTORC2 in adipose tissue are hypothermic and sensitive to cold. mTORC2 in BAT stimulates cold‐induced glucose uptake and glycolysis via Akt. Restoration of glucose uptake in BAT of AdRiKO mice restores temperature homeostasis. Abstract : Albert et al show that β‐adrenergic stimulation activates mTORC2 in brown adipocytes. Active mTORC2 signaling in BAT is required for cold‐induced stimulation of glucose uptake and glycolysis to maintain temperature homeostasis upon cold stress.